Development Of E-Comic Learning Media On The Topic Of The Human Digestive System - Udayani, Ni Komang Restu Tri Krisnanti; Wibawa, I Made Citra; Rati, Ni Wayan (Universitas Pendidikan Ganesha, 2021)
Learning during a pandemic make teachers have to change learning that is usually carried out face-to-face into online learning that is still fun for students. Learning media during online learning will help teachers deliver learning material more creatively to become more enjoyable, and students easily understand the learning material. This study aims to develop e-comic learning media on the topic of the human digestive system. This research is a type of development research using the ADDIE model. However, this study's implementation and evaluation stages cannot be carried out due to the COVID-19 pandemic, limited time, resources, and costs. Thus, in this study, only the analysis, design, and development stages were carried out. The subjects in this study were two media experts, two material experts, and two practitioners. The data collected in this study used a questionnaire method by analyzing the e-comic learning media. The data from the validation results from the experts were then analyzed using the mean formula to find out the average validity score of e-comic learning media on the topic of the human digestive system. The analysis results show that the average validation score of e-comic learning media on the topic of the human digestive system is 4.65 with very good qualifications, and material validation is 4.57 with very good qualifications. So, e-comic learning media on the topic of the human digestive system are declared valid and have very good qualifications.